2020
DOI: 10.3390/su12187579
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Social Sustainability in Urban Regeneration Processes. An Application of the Social Multi-Criteria Evaluation

Abstract: The concept of sustainability is widely seen as fundamental to set up urban and territorial transformations. Sustainable development is a multidimensional and multi-perspective process that deals with the environmental, economic, and social dimensions, with the aim to find a balance among these. Despite this growing attention to sustainability the social perspective has been the less explored of these dimensions and only recently it is receiving consideration due the Sustainable Development Goals (SDGs) that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 67 publications
2
18
0
1
Order By: Relevance
“…Social sustainability should be an integral part of all urban regeneration initiatives, but it is only recently that it has been increasingly taken into account with the Sustainable Development Goals (SDGs) [6]. This trend is also described in a study by the Western Australian Council of Social Service (WACOSS), which found that while considerable work has been conducted "on the environmental and economic aspects, the social has tended to fall off the sustainability agenda" [7].…”
Section: Literature Review and Justificationmentioning
confidence: 99%
“…Social sustainability should be an integral part of all urban regeneration initiatives, but it is only recently that it has been increasingly taken into account with the Sustainable Development Goals (SDGs) [6]. This trend is also described in a study by the Western Australian Council of Social Service (WACOSS), which found that while considerable work has been conducted "on the environmental and economic aspects, the social has tended to fall off the sustainability agenda" [7].…”
Section: Literature Review and Justificationmentioning
confidence: 99%
“…By considering MHN rehabilitation challenges, it is recognised that the application of architectural design to advance social equality can be a link for balancing and further strengthening all components of sustainable urban development. In the research of these aspects, the dominant engagement of multi-methodological approaches is recognised: (1) For exploring the social sustainability related to urban regeneration processes [25]; (2) for addressing spatial inequality through neighbourhood-based regeneration and community participation [26]; and (3) for developing the concept of socially integrative city aligned with the regeneration policies [27]. Through defining social equity in the context of urban resilience, Meerow et al [28] identified a tripartite framework of social equity that includes distributional, recognitional and procedural equity dimensions: (1) equitable distribution of resources, (2) acknowledgement of different social groups, and (3) equitable involvement in participatory processes.…”
Section: Mhn Rehabilitation Challengesmentioning
confidence: 99%
“…The obtained result can be analyzed to test its robustness through a Sensitivity Analysis and its level of consensus through implementing a Social Multi-Criteria [46].…”
Section: Choice Of the Favorable Reuse Alternativementioning
confidence: 99%
“…The financial sustainability of the reuse project can be assessed by referring to two profitability indicators [46]. The former is the Net Present Value (NPV), given by the sum of the present values of the incoming and outgoing individual cash flows, as shown in Equation ( 2…”
Section: Financial Sustainability Assessmentmentioning
confidence: 99%